New means to an end: mRNA export activity impacts alternative polyadenylation - Shin, Jihae (Transcription, 2019)
Gene expression involves multiple co- and post-transcriptional processes that have been increasingly found intertwined. A recent work by our groups (Chen et al. Mol Cell, 2019) indicates that expression of alternative polyadenylation isoforms in mammalian cells can be controlled by nuclear export activities. This regulation has distinct impacts on genes having different sizes and nucleotide contents, and involves RNA polymerase II distribution toward the 3ʹ end of genes. This work raises a number of intriguing questions concerning how 3ʹ end processing and nuclear export are integrated and how their regulation feeds back to transcription.